Design of wave-optical structured substrates for ultra-thin perovskite solar cells. (September 2020) - Haque, Sirazul; Alexandre, Miguel; Mendes, Manuel J.; Águas, Hugo; Fortunato, Elvira; Martins, Rodrigo
Highlights: 1) Industrially-attractive photonic substrates optimized for perovskite solar cells. 2) Wave-optical structuring provides broadband light-trapping via anti-reflection and scattering. 3) Outstanding 25% photocurrent enhancement attained, close to Lambertian limit. 4) Omni-directional performance enhancement demonstrated for large angular range (0°–70°). 5) Optically-enhanced cells with ultra-thin 300nm-perovskite outperform flat devices with 500nm-perovskite. Abstract: Photonic micro/nano-structures in the wave-optics regime have shown to be a promising strategy for effective broadband light capture in ultra-thin devices, opening a window of opportunity for cheap, efficient, lightweight and flexible photovoltaics (PV). Here we design, from an optical standpoint, a novel industrially-attractive concept where light trapping is obtained by conformably depositing the solar cell materials onto previously-patterned photonic substrates. This solution is applied and optimized for perovskite solar cells (PSCs) with distinct thicknesses of the perovskite absorber - the conventional (500 nm) and ultra-thin (300 nm) in view of enhanced flexibility - yielding photocurrent improvements up to 22.8% in superstrate cell configuration and 24.4% in substrate-type configuration; thereby coming relatively close to the fundamental Lambertian limits. Furthermore, these structures also show an omni-direction optical response for incidence angles up to 70° for all cases, therefore demonstrating the viability of this light trapping method for implementation in flexible PV devices operating under bending. The photonic-enhanced ultra-thin solar cells designed here ultimately support the reduction of material usage in PSC technology, which is especially beneficial to mitigate lead usage, without impacting the device's performance. Graphical abstract: Image, graphical abstract